Structural and chemical changes of grape seed extract after thermal processing and its use in rainbow trout (Oncorhynchus mykiss) diets as an organic feed supplement - Kesbiç, Osman Sabri; Yigit, Murat (Elsevier BV, 2019)
Abstract The present study aimed to evaluate physicochemical properties and structural variations of grape seed extract exposed to thermal process during feed production, and the use of grape seed extract in rainbow trout diets as a sustainable organic fish feed supplement. Structural changes of grape seed extract granules were observed under a scanning electron microscope, and analyzed using HPLC/UV and GC/MS. Following thermal process, an increase in the granular size of grape seed was observed and cracks were formed on the granules. In the flavor analysis performed using a GC/MS device, totally nine volatile compounds were identified and three of them were palmitic, linoleic and oleic fatty acids. Thermal processing treatment decreased (+)-catechin amount in grape seed extract from 0.667 to 0.557 mg/L, whereas (−)-epicatechin increased from 0.819 to 1.156 mg/L. As a second step of the study, grape seed extract, a waste product of the wine industry, was supplemented in rainbow trout (Oncorhynchus mykiss) diets at concentrations of 0, 0.5, 1, and 2‰ and given to experimental fish for a period of 90 days. Feed and protein utilization coefficients as well as growth performance of the experimental fish fed diets containing grape seed extracts differed significantly (P   .05), however protein ratio significantly increased in the 0.5‰ grape seed extract group compared to the control (P
Keywords: 2. Zero hunger; 6. Clean water; 12. Responsible consumption